Papillary fill response in single‐tooth implants using abutments of different geometry. Issue 12 (6th April 2015) - Patil, Ratnadeep; den Hartog, Laurens; Dilbaghi, Anjali; de Jong, Bart; Kerdijk, Wouter; Cune, Marco S.
Abstract: Objective: To evaluate the influence of abutment geometry on papillary fill in the esthetic zone in a delayed crown protocol. Materials and methods: Twenty‐six subjects received two non‐adjacent endosseous implants in the esthetic zone. Functional temporary crowns were installed 17–19 weeks later, using conventional (control) and curved (experimental) abutments. The abutments were randomized in each patient independently. Final crowns were cemented after 2 months (T0). Standard intraoral photographs and radiographs were made to evaluate papillary fill after 12 months (T12). The interproximal papilla fill was measured by means of the papilla index score (PIS) and related to the maximum bone level between the implant and the adjacent root as well as the peri‐implant marginal bone level at T12, both measured radiographically. Results: No statistically significant difference between the experimental and the control group could be demonstrated ( P  = 0.25). Ordinal regression analysis showed a positive correlation between the maximum bone level and papilla fill ( P  < 0.01) and a negative correlation between the peri‐implant marginal bone level and papilla fill ( P  < 0.05). Conclusion: A concave abutment does not exhibit a better fill of the papilla compared with a straight abutment in single‐tooth implant placement using a delayed protocol in the esthetic zone after 12 months of function.